Impact of COVID-19 on Prostate Cancer Management: Guidelines for Urologists - Zachary Dovey (European Urology Open Science, 2020)
Context: The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic has resulted in a global health emergency, the like of which has never been seen before. Prostate cancer (PCa) services across the globe have been on hold due to changing medical and surgical priorities. There is also epidemiological evidence that PCa patients have increased incidence and mortality from SARS-CoV-2 infection due to gender differences, age, and higher propensity for risk factors (eg, respiratory disease, obesity, hypertension, and smoking status). Objective: To contribute to the emerging body of knowledge on the risks of SARS-CoV-2 infection to PCa patients and, in the face of PCa treatment delays, provide evidence-based recommendations for ongoing management of specific PCa patient groups. Evidence acquisition: A literature search was performed using all sources (MEDLINE, EMBASE, ScienceDirect, Cochrane Libraries, and Web of Science) as well as the media to harness emerging data on the SARS-CoV-2 pandemic and its influence on PCa. Eligibility criteria were originality of data and relevance to PCa management. The authors note that during these unprecedented times, retrospective data are constantly being updated from multiple sources globally. Evidence synthesis: A total of 72 articles and data sources were found initially. Owing to repetition, lack of originality, or nonrelevance, six articles were rejected, leaving 23 retrospective studies, seven basic science research articles, 15 societal and journal guidelines, and 21 epidemiological data sources, from countries at different stages of SARS-CoV-2 pandemic. These were analyzed qualitatively to produce evidence-based guidelines for the management of PCa patients at different stages of the patient journey, with strategies to reduce the risk of viral spread. Conclusions: PCa patients may have an increased risk of SARS-CoV-2 infection as well as morbidity and mortality if infected. Once appropriately triaged, and to reduce viral spread, PCa patients can have surveillance by telemedicine, and institute lifestyle changes and social quarantining measures. If risk stratification suggests that treatment should be planned, androgen deprivation therapy can be started, or potentially surgery or radiation therapy is possible on a case-by-case basis. Patient summary: Prostate cancer patients can be followed up remotely until the severe acute respiratory syndrome coronavirus 2 pandemic resolves, but higher-risk cases may have treatment expedited to limit any negative impact on prostate cancer outcomes.